Curcumin-loaded nanostructured systems for treatment of leishmaniasis: a review - Dourado, Douglas; Silva Medeiros, Thayse; do Nascimento Alencar, Éverton; Matos Sales, Edijane; Formiga, Fábio Rocha (Beilstein Journal of Nanotechnology, 2024)
Leishmaniasis is a neglected tropical disease that has affected more than 350 million people worldwide and can manifest itself in three different forms: cutaneous, mucocutaneous, or visceral. Furthermore, the current treatment options have drawbacks which compromise efficacy and patient compliance. To face this global health concern, new alternatives for the treatment of leishmaniasis have been explored. Curcumin, a polyphenol obtained from the rhizome of turmeric, exhibits leishmanicidal activity against different species of Leishmania spp. Although its mechanism of action has not yet been fully elucidated, its leishmanicidal potential may be associated with its antioxidant and anti-inflammatory properties. However, it has limitations that compromise its clinical use. Conversely, nanotechnology has been used as a tool for solving biopharmaceutical challenges associated with drugs, such as curcumin. From a drug delivery standpoint, nanocarriers (1–1000 nm) can improve stability, increase solubility, promote intracellular delivery, and increase biological activity. Thus, this review offers a deep look into curcumin-loaded nanocarriers intended for the treatment of leishmaniasis.
Keywords: antiparasitic; Curcuma longa; curcuminoids; leishmaniasis; nanocarriers; neglected tropical diseases